2021
DOI: 10.1371/journal.pone.0255644
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early corticosteroids on 60-day mortality in critically ill patients with COVID-19: A multicenter cohort study of the OUTCOMEREA network

Abstract: Objectives In severe COVID-19 pneumonia, the appropriate timing and dosing of corticosteroids (CS) is not known. Patient subgroups for which CS could be more beneficial also need appraisal. The aim of this study was to assess the effect of early CS in COVID-19 pneumonia patients admitted to the ICU on the occurrence of 60-day mortality, ICU-acquired-bloodstream infections(ICU-BSI), and hospital-acquired pneumonia and ventilator-associated pneumonia(HAP-VAP). Methods We included patients with COVID-19 pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…Hence, we wanted to focus specifically on hospitalized COVID-19 patients requiring supplemental oxygen therapy to assess whether early use of steroids would be beneficial, and to identify the threshold of illness at which steroids would be helpful. Our study results are consistent with other observational studies that showed no difference in risk of intubation or mortality between non-critically ill hospitalized patients who received versus those that did not receive corticosteroids [ 11 , 15 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, we wanted to focus specifically on hospitalized COVID-19 patients requiring supplemental oxygen therapy to assess whether early use of steroids would be beneficial, and to identify the threshold of illness at which steroids would be helpful. Our study results are consistent with other observational studies that showed no difference in risk of intubation or mortality between non-critically ill hospitalized patients who received versus those that did not receive corticosteroids [ 11 , 15 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…This selection bias towards the sickest patients could possibly explain the difference in the corticosteroid impact on outcomes compared to recent prospective trials. Of note, corticosteroids have recently been shown to exert less beneficial effects in certain patient subgroups, including elderly patients [ 27 ] and those with a hypo-inflammatory phenotype [ 28 , 29 ]. As expressed by De Backer et al, the beneficial effects on the Day-28 mortality endpoint, relatively short in duration, may not necessarily translate into longer-term benefits [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, COVID-19-associated and steroid-induced immunomodulation also implies superinfection because of other opportunistic pathogens. Patients treated with dexamethasone had reduced ICU length of stay, more ventilator-free days but similar mortality regardless of the timing of administration [ 48 ]. A true concern also exists about fungal superinfections that could be associated with lung abscesses.…”
Section: Is It Really An Issue ?mentioning
confidence: 99%